The hobbit - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; Wyatt, David (London : Harper Collins, 1998)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to share in an adventure from which he may never return.
7-9
Keywords: Fiction, English